A Comparison Study on Types of PV for Grid Connected Photovoltaic Power - Renuga Verayiah; Anusiya Iyadurai (Institute of Advanced Engineering and Science, 2017)
Grid connected photovoltaic (PV) power systems is today’s breakthrough for renewable energy source in electricity generation Grid-connected photovoltaic (PV) power systems have the advantage of more effective utilization for highest renewable source of electricity generation and tendency to continual growth in the next years. The output performance grid connected photovoltaic (PV) power systems is influenced by the impact of cell temperature or ambient temperature and solar irradiance of the solar module. This paper highlights the effect of output energy of solar module by implementing different types of solar module technology and selecting the highest energy output of the module technology for modelling and simulating the design of grid connected photovoltaic (PV) power system using Matlab/Simulink.